Violation of specific indicators pigment and lipid metabolism in experimental pneumonia in an immobilization stress and correction of corvitin - N. M. Ferenc (Kazimierz Wielki University, 2015)
Ferenc N. M. Violation of specific indicators pigment and lipid metabolism in experimental pneumonia in an immobilization stress and correction of corvitin. Journal of Education, Health and Sport. 2015;5(9):709-713. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32430 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A709-713 https://pbn.nauka.gov.pl/works/658656 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   UDC: 61624 - 002 -036.11 - 092: 612,019   VIOLATION OF SPECIFIC INDICATORS PIGMENT AND LIPID METABOLISM IN EXPERIMENTAL PNEUMONIA IN AN IMMOBILIZATION STRESS AND CORRECTION OF CORVITIN   N. M. Ferenc   Lviv National Medical University Daniel Galician, Lviv, Ukraine   Abstract   The aim of study was to investigate the features change cholesterol and bilirubin in the blood serum of guinea pigs (males) with experimental pneumonia (EP) under conditions of immobilization stress (IS) and prove the feasibility of Corvitin. The study was conducted on 48 guinea pigs (males) were divided into 6 groups. The research results make it possible to detect liver damage in terms of IS EP and in violation of its functional state. Application domestic preparation Corvitin led to a significant reduction in the changed parameters bilirubin and cholesterol under conditions of formation of EP and IP, which indicates its positive corrective effect.   Keywords: experimental pneumonia, stress, liver, cholesterol, bilirubin.